2018
DOI: 10.21010/ajid.v12i1s.7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Psychological Well-Being in Boosting Immune Response: An Optimal Effort for Tackling Infection

Abstract: Background: Many attempts have been made to improve human body resistance towards infection. These attempts were exemplified by promotion of hygiene and the use of antiseptic ingredients, pharmaceutical compounds, and vaccines. To prove an aspect which intentionally less explored was attempt to boosting the host immune responses by creating a psychological balance, which was important aspect of psychological well-being. Material and Method: These article reviews searched and compiled using database Google Scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Again, the suppression state of immunity may potentially impact the fatigue level and loss of vigor. Several studies have revealed the active association between the psychological condition and immune systems [39-41]. Notably, a recent study showed a relationship among the alteration of immunity, inflammation in central nervous systems, and psychiatric disorders [42].…”
Section: Discussionmentioning
confidence: 99%
“…Again, the suppression state of immunity may potentially impact the fatigue level and loss of vigor. Several studies have revealed the active association between the psychological condition and immune systems [39-41]. Notably, a recent study showed a relationship among the alteration of immunity, inflammation in central nervous systems, and psychiatric disorders [42].…”
Section: Discussionmentioning
confidence: 99%
“…Current clinical research indicates that cognitive drumming accelerates physical healing, boosts the immune system, and produces feelings of well-being through the release of emotional trauma [6,7]. Additionally, clinical studies have proven that cognitive drumming has calming, focusing, and healing effects on individuals including children diagnosed with autism, combat veterans, emotionally disturbed teens, recovering addicts, trauma patients, prisoners, and homeless individuals [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%